Nickel ions modified CoMg nanophotocatalysts for solar light-driven degradation of antimicrobial pharmaceutical effluents. (June 2022) - Jasrotia, Rohit; Verma, Ankit; Verma, Ritesh; Kumar, Sachin; Ahmed, Jahangeer; Krishan, Bal; Kumari, Swati; Tamboli, Asiya M.; Sharma, Swati; Kalia, Susheel
Abstract: Unutilized pharmaceutical antibiotics and waste have become a severe hazard to human health and aquatic life due to their carcinogenic, mutagenic, and poisonous properties. Nickel modified CoMg magnetic nanophotocatalysts with a chemical composition of Co0.65 Mg0.35-x Nix Fe2 O4 (x = 0, 0.01, 0.02, 0.03) were fabricated by sol-gel auto-combustion approach. The prepared nanoparticles (NPs) were used for solar light-driven photodegradation of amoxicillin pharmaceutical effluent. XRD diffraction patterns data identify the spinel cubic-like structures with Fd3m symmetry. No different phases were seen within XRD patterns of prepared magnetic NPs. FESEM confirms the formation of agglomerated and spherical NPs with an average grain size of 349 and 351 nm for unmodified (S1) and modified (S3) samples, respectively. The TEM investigation analyzed the particle size distribution, which shows the formation of aggregated and spherical NPs with an average particle size of 32 nm for the S1 specimen. FTIR spectra reported stretching vibrations within the metal‑oxygen complexes at the interstitial sites. The photocatalytic efficiency of synthesized nanoferrites was utilized to degrade the pharmaceutical amoxicillin effluent. The prepared nickel-modified nanophotocatalyst (S4) shows a maximum degradation efficiency of 95.05% with a rate constant of 0.0204 min −1 . Synthesized nanophotocatalysts work as an excellent antibacterial agent against the Pseudomonas aeruginosa and Bacillus subtilis bacteria extensively, demonstrating that the S4 specimen showed the highest zone of inhibition against the Pseudomonas aeruginosa . In contrast, both the S3 and S4 specimens showed a maximum zone of inhibition against the Bacillus subtilis compared to other NPs. Graphical abstract: Unlabelled Image Highlights: Synthesis of nickel ions modified CoMg nanophotocatalysts. Ni-modified CoMg nanoparticles show a maximum degradation efficiency of 95.05%. Nanoparticles behave like potential photocatalysts due to their reusability. Nanoparticles exhibit antibacterial activity against P. aeruginosa and B. subtilis .